The Role of Kediri Regency Government Policies in Tourism Development (A Case Study of Kampung Madu Tourism Village) - Sonia Yulida; Agus Machfud Fauzi (Media Hukum Indonesia (MHI), 2026)
The development of tourism villages has become one of the strategies of local governments to promote community-based tourism development. Kampung Madu Tourism Village in Bringin Village, Badas District, Kediri Regency is an educational tourism destination based on honeybee cultivation and has significant potential to support the local economy. However, its development still faces several challenges, such as limited infrastructure, human resource capacity, and suboptimal digital promotion. This study aims to analyze the role of Kediri Regency government policies in the development of Kampung Madu Tourism Village.This research employs a descriptive qualitative approach with data collection techniques including in-depth interviews, field observations, and documentation. The research informants consist of village government officials, tourism village managers, local communities, the Kediri Regency Tourism Office, and members of the Regional House of Representatives (DPRD). Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that government policies play roles as facilitators, regulators, and mediators in the development of the tourism village. The village government plays a role in drafting village regulations, strengthening institutional capacity, and increasing community participation, while the regency government contributes through human resource training, tourism promotion, and cross-sector collaboration. Nevertheless, policy implementation still faces several challenges, including budget limitations, the technological capacity of the managers, and uneven community participation.